Is the WTO open and transparent? : a discussion of the relationship of the WTO with non-governmental organisations and civil society's claims for more transparency and public participation. - MARCEAU, Gabrielle (1999)
Discusses the actions that the WTO members and the WTO Secretariat have taken to increase transparency, to delineate the legal parameters of WTO agreements in this area and consequently, to highlight the existing limitations that need to be pushed forward should members decide to change the situation as it stands today.